Micro and nanotechnology for regenerative medicine : cell tracking and engineering - Liu, Shiying (2017)
Regenerative medicine is providing a promising treatment method for degenerative diseases, and has been extensively investigated in recent decades for bone, skin, cartilage, neurons, blood vessels, skin regeneration, and so on. One of the most important branches is to exploit multi- potent stem cells to differentiate into targeted tissues and organs. Mesenchymal stem cells (MSCs) have been identified and widely explored as a promising and main source for regenerative medicine, with great differentiation potentials into osteocytes, adipocytes, and chondrocytes but less concern of ethical issues. However, a tough problem is to track the location, migration, fate and distribution of these transplanted stem cells. Clearer understanding about these will help instruct the optimum cell dosage, transplantation time, and evaluating efficacy. It is imperative to develop a photostable probe with excellent biocompatibility to track the MSCs for a long-term without affecting the cell proliferation and potency. Another issue which is targeted in this thesis is to develop an effective and conveniently used drug delivery system for treatment of keloid scars to achieve skin regeneration. Keloid scars, as a complex abnormal scar, cause not only aesthetic disfigure to the patients, but also have leaded to pruritus, infection, and much distress. Traditional treatments include surgery removal, silicone or pressure dressings, hypodermic injections of drugs like corticosteroid, fluorouracil (5-FU), and so on. However, these methods may result in pain, infections, and adverse effects as well as less compliance to patients. Transdermal delivery route by microneedles can provide a non-invasive method for delivering drugs with low cost and conveniences to patients. In this thesis, a new type of highly fluorescent and bioresorbable polymeric nanoparticles were prepared through nanoprecipitation from a well-defined polymer, PCL–DPP–PCL, in the presence of Pluronic® 127 as the stabilizer. Covalent insertion of DPP as a highly fluorescent moiety into the middle of each PCL chain and generated steric effect effectively suppress the π–π aggregation of DPP in the PCL matrix to reduce the bleaching effect. The nanoparticles prepared through a nanoprecipitation process were highly fluorescent and could be internalized by MSCs with little cytotoxicity. Most importantly, the PCL–DPP–PCL nanoparticles exhibited significantly enhanced photostability compared to several commercial organic fluorophores, the physically blended DPPHT/PCL nanoparticles and Qtracker® for imaging stem cells. Secondly, these PCL-DPP-PCL nanoparticles were applied for long-term tracking of mesenchymal stem cell differentiation. In vitro cell experiments exhibited the nanoparticles labelling did not compromise the cell viability and demonstrated different performances on the multilineage potency of the MSCs during differentiation. Specifically, compared to the unlabeled control cells, this probe labeling compromised MSC osteogenic differentiation, but didn’t show any negative effects for adipogenic and chondrogenic as verified by gene expressions and histological staining. Furthermore, these fluorescent probes were able to maintain their strong fluorescence intensity even after 4 weeks of differentiation. This study demonstrated that PCL-DPPPCL nanoparticles could be used for long-term cell tracking in MSC differentiation into adipogenic and chondrogenic lineages. Finally, regarding to the keloid scar treatment issue in the regenerative medicine field, we introduced a facile, effective, and gentle strategy to load PEGDA microneedles with connexin mimetic peptides (Gap26) without compromising peptide potency through the swelling effect of PEGDA in the aqueous solution. By regulating UV crosslinking time, the swelling ratio, and mesh size of PEGDA microneedles can be controlled. Gap 26 was loaded into the PEGDA microneedles to suppress the gap junction-based intercellular communication between keloid fibroblasts which leads to reduced collagen I expression in an ex vivo model. This exhibits its therapeutic potentials for keloid scar.